The Deep Structure of the Kimberlite Pipe Volchya in the Arkhangelsk Diamond Province and Controlling Faults Based on Passive Seismic and Radiological Methods (Northwest Russia) - Konstantin Danilov; Evgeny Yakovlev; Andrey Puchkov; Vladimir Bykov; Alexander Katorin (Applied Sciences)
The successful prospecting of kimberlite pipes is dependent upon a comprehensive understanding of the deep structures of the pipes and the host geological formation. This is a challenging task, given the complex nature of diamond deposits, the small size of pipes in the plan, the absence of stable features in potential fields, etc. As a consequence, the allocation of control structures is practically not used in exploration work. In this regard, the Arkhangelsk diamond province (NW Russia) is distinguished by the considerable overburden thickness, which presents a significant challenge for the application of geophysical methods. It is thus imperative to devise novel methodologies for conducting investigations. In order to achieve this, a set of methods was employed, including microseismic sounding, passive seismic interferometry, and radon emanation mapping. This set of methods has previously been tested only on a few pipes and has not previously been employed in the Griba deposit. The Volchya pipe was selected as the test object due to its proximity to the Griba pipe. The findings revealed that the pipe displayed a more complex configuration than was previously postulated. The controlling faults were found to be oriented in a southwesterly to northwesterly direction and to exhibit a contrasting narrow vertical structure at depths greater than 400 m. Further identification of control structures by the proposed set of methods can increase the efficiency of diamond prospecting.